2004
DOI: 10.1155/s0962935104000559
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil infiltration, gastric juice and serum eosinophil cationic protein levels in Helicobacter pylori‐associated chronic gastritis and gastric ulcer

Abstract: INTRODUCTION: Helicobacter pylori is one of the main causes of gastroduodenal diseases, such as chronic gastritis and peptic ulcer. It has been shown that eosinophils increase in the stomach in H. pylori infection. Eosinophilic cationic protein (ECP) is a cytotoxic molecule secreted by the activated eosinophils. However, there are no sufficient data about the role of ECP in H. pylori infection and its effect on ulcer development. In this study we investigated the gastric eosinophilic infiltration, gastric juic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 31 publications
4
18
0
3
Order By: Relevance
“…Although the percent of blood EOS count is higher in IgG positive group than IgG negative group, the correlation between anti-HP IgG antibody titers and EOS count is not significant in the present study. There are several studies that support our results in HP infection [21,22]. Activation of eosinophils seems to contribute to the pathophysiology of several inflammatory conditions [23].…”
Section: The Conclusionsupporting
confidence: 86%
See 2 more Smart Citations
“…Although the percent of blood EOS count is higher in IgG positive group than IgG negative group, the correlation between anti-HP IgG antibody titers and EOS count is not significant in the present study. There are several studies that support our results in HP infection [21,22]. Activation of eosinophils seems to contribute to the pathophysiology of several inflammatory conditions [23].…”
Section: The Conclusionsupporting
confidence: 86%
“…The role of eosinophils in the pathogenesis of HP-associated gastritis and ulcer is not explained. One of the major constituents of the granule matrix is the eosinophil cationic protein [22]. Aydemir et al [22] reported that gastric mucosal eosinophil infiltration and the gastric juice ECP level were apparently greater in H. pylori infected subjects, however, serum ECP level no significant between H. pylori infected and non-infected groups.…”
Section: The Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent findings were confirmed in a larger sample size by a later study with specimens from 44 H. pylori-positive patients and 20 H. pylori-negative patients [117]. In specimens of chronic H. pylori gastritis, the severity of gastritis was significantly correlated with that of eosinophil infiltration [116], although no difference in the severity of eosinophil infiltration was observed between gastritis with ulcer and those without gastric ulcer among H. pylori-positive patients [117].…”
Section: Interaction Between Gastric Epithelial Cells and Eosinophilssupporting
confidence: 58%
“…[1][2][3] The bacterial derivatives cause infl ammatory infi ltration in the stomach tissue consisting of neutrophil and eosinophil leukocytes, lymphocytes, plasma cells, and macrophages. [4][5][6] Several studies have indicated that H. pylori infection is accompanied by an infl ammatory response associated with gastric mucosal damage through the activation of polymorphonuclear neutrophil leukocytes. 7 In these cells the activation of enzymatic systems such as NADPH oxidase, inducible nitric oxide synthase, and myeloperoxidase form reactive species of oxygen and nitrogen, precursors of the production of hypochlorite, monochloramine, and peroxinitrite, with oxidative and cytolytic effects on the gastric mucosa.…”
Section: Introductionmentioning
confidence: 99%